An Option for the Theoretical Foundation of Corporate Social Responsibility - Jiménez Montero, Daniel (2011)
The Christian Philosophical anthropology indicates that human beings are capable of governing their acts because they are equipped with intelligence –that enables them to understand the reality in force, including their own existence– and with willpower –that enables them to want to do the things our intelligence has considered as good- before this panorama, ethics emerges as a practical science responsible for assessingthe kindness of human acts, with the purpose of enabling human beings with an instrument that guides them in a right and opportune way during the ordinary course of their life. As enterprise activity represents a typical human act, it also should be subjected to ethical evaluation in this particular case, the company’s action is suited to be evaluated based on three fundamental principles: intrinsic kindness, impartialityand proportionality; among othersunder this perspective, ethic’s radius of action within enterprise activity is whole,including the ranges where human acts take place. Therefore it should includeenterprise procedures that are related to its clients, suppliers, contributing members, owners and other people and organizations present in the enterprise’s surroundings The concept of corporate social responsibility that is valid in the Costa Rican enterprise sector encompasses various meanings before this situation, the writing of the present article emerges as a contribution from one particular stand point, accomplished with the intention of enriching the fore mentioned concept